Evaluasi Program Penanggulangan Gizi Buruk Pada Balita di Dinas Kesehatan, Pengendalian Penduduk dan Keluarga Berencana Kota Tanjungpinang - Delfi Heni Susanti; Rumzi Samin; Okparizan Okparizan (Doktrin:Jurnal Dunia Ilmu Hukum dan Politik, 2023)
Nutritional problems in infants and toddlers are still a major problem in community administration, one of which is the problem of malnutrition. Tanjungpinang City still finds cases of toddlers with malnutrition disorders, among others, malnutrition, undernutrition and stunting. cases of malnutrition in Tanjungpinang City have increased over the past three years. In 2020 there were 97 toddlers, in 2021 there were 121 toddlers and in 2022 it rose to 245 toddlers. The purpose of this study is to Evaluate the Poor Nutrition Management Program in Toddlers at the Tanjungpinang City Health Office. Researchers use a qualitative descriptive approach. The results of the program evaluation show how the achievement of the implementation of the malnutrition mitigation program carried out by the Tanjungpinang City Health Office. The context indicator explains the background of the program and the strategy carried out by the Health Office has run optimally to achieve program goals. Furthermore, input indicators still require complete human resources and infrastructure so that malnutrition management programs can run effectively. Then, the HR process indicators in this program have been running through coordination so that activities can run regularly but there are still some things that need to be considered in increasing participation and knowledge about parenting. Furthermore, product indicators are evaluated in running the program, but there are still some negative sides that still think that handling nutritional problems is a health task. The conclusion of the evaluation of the malnutrition mitigation program by the Tanjungpinang Health Office is that the malnutrition program is effective enough but has not been optimally implemented. Suggestions as an improvement effort are to increase community understanding of the program, strive for the fulfillment of additional feeding for all toddlers, fulfill program training, add officers and improve training.